Segmentation Of Fingerprint Image Using Block-Wise Coherence Algorithm - Saparudin - (Universitas Sriwijaya, 2010)
The Segmentation of fingerprint image is an important step in the fingerprint identification. The objective of the fingerprint image segmentation is to separating the foreground regions from the background regions. Accurate segmentation of fingerprint images influences directly the performance of minutiae extraction like minutiae and singular points. In this paper, an algorithm for the segmentation of fingerprint image is presented. The method uses block-wise coherence. Fingerprint data has been taken from NIST databases 14. The segmentation algorithm has been trained on fingerprints of this database, but not on these particular fingerprints. Human inspection shows that the block-wise coherence algorithm provides satisfactory result. Keyword: fingerprint image segmentation, block-wise, coherence, minutiae, singular point.